The cost efficiency and competition relationship: Evidence from Saudi Arabian banks and non-structural approaches to analysis - Hind Alnafisah; Lama Alwohaibi (Economies, 2023)
Over the last two decades, the regulators of the financial services sector in Saudi Arabia have aimed to develop a level of fair competition in the provision of banking services across the country. This paper utilizes non-structural approaches, the H-statistic developed by, and the Granger causality test. The second approach involves determining the Granger-based causal relationship between banks' cost efficiency and competition via data envelope analysis (DEA) using the generalized method of moments (GMM) panel. The study's data were drawn from 11 traditional banks in Saudi Arabia, covering the period from 2015 to 2021 (yearly data). The results of the non-structural approach, i.e., the H-statistic, demonstrate that the average fund rate had a positive effect on competition; however, the physical capital price index, the index of leverage, and the credit risk negatively affect the total revenue. Furthermore, a positive H-statistic value reflects the positive causality between competition and cost efficiency (higher efficiency results in a higher level of competition). The DEA results indicate that competition in the year 2021 was influenced by the competition level of the previous year (2020); moreover, the relationship between the previous year's cost efficiency Granger value, the greater availability, and the lower prices of banking products had a significant influence on the competition in the years under consideration (since a positive significant result from the test is available), which reflects the higher level of market structure and the greater availability and lower prices of banking products. Cost efficiency in the year 2021 was also positively influenced by the cost efficiency level of the previous year (2020), with competition forcing efficiency via the cutting of costs.
Keywords: 330; concentration ratio; monopolistic competition; cost efficiency; banking sector in SaudiArabia